2019
DOI: 10.5324/barn.v37i3-4.3384
|View full text |Cite
|
Sign up to set email alerts
|

”Det er godt sådan i det hele taget at kunne sige, hvad man vil og ikke vil” – Børn med funktionshæmning og deres refleksioner omkring deltagelse og indflydelse på eget liv

Abstract: When it comes to children with disabilities and their reflections on participation and influence intheir everyday lives, there is very little research. The study has a phenomenological-hermeneuticapproach and participatory methods over time. Together with three children aged 9–12 the studyexplores their experiences of participation and influence in their everyday lives based on article12 in the UN Convention on the Rights of the Child. The children’s reflections are connected to therecognition theory of Axel H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…When looking at research studies concerning children with disabilities and their views and experiences with participation and influence, the children most often express that they don't have a say or only are involved in small decisions (Andersen & Dolva, 2015;Stafford et al, 2003;Young et al, 2006). However, some studies have identified that the children accept and/or understand why it is so and adapt to it (Andersen et al, 2019;Coyne & Gallagher, 2011;Stafford et al, 2003). Meanwhile, studies show that children with disabilities state that it is important to be able to express one's opinions (Andersen et al, 2019;Cavet & Sloper, 2004;Mårtenson & Fägerskiöld, 2008;Stafford et al, 2003).…”
Section: Protection Versus Influencementioning
confidence: 99%
See 4 more Smart Citations
“…When looking at research studies concerning children with disabilities and their views and experiences with participation and influence, the children most often express that they don't have a say or only are involved in small decisions (Andersen & Dolva, 2015;Stafford et al, 2003;Young et al, 2006). However, some studies have identified that the children accept and/or understand why it is so and adapt to it (Andersen et al, 2019;Coyne & Gallagher, 2011;Stafford et al, 2003). Meanwhile, studies show that children with disabilities state that it is important to be able to express one's opinions (Andersen et al, 2019;Cavet & Sloper, 2004;Mårtenson & Fägerskiöld, 2008;Stafford et al, 2003).…”
Section: Protection Versus Influencementioning
confidence: 99%
“…However, some studies have identified that the children accept and/or understand why it is so and adapt to it (Andersen et al, 2019;Coyne & Gallagher, 2011;Stafford et al, 2003). Meanwhile, studies show that children with disabilities state that it is important to be able to express one's opinions (Andersen et al, 2019;Cavet & Sloper, 2004;Mårtenson & Fägerskiöld, 2008;Stafford et al, 2003). However, some children with disabilities believe that it is more important to be recognized rather than being the one in charge of decisions (Andersen et al, 2019;Coyne & Gallagher, 2011;Stafford et al, 2003).…”
Section: Protection Versus Influencementioning
confidence: 99%
See 3 more Smart Citations